Pengaruh integriti kepemimpinan terhadap pelaksanaan pengurusan kualiti menyeluruh di Institusi Pendidikan Tinggi MARA. - Mumtaz Begam Bt Abdul Kadir,; Norzaini Azman,; Mohammed Sani Ibrahim, (Universiti Kebangsaan Malaysia, 2010)
Leadership plays an important role in determining the quality and excellence of an institution. Leadership must have firm political will, vision, and clear targets; it must hold fast to the principles of honesty, efficiency and trustworthiness, be exemplary, prudent, as well as people-friendly (PIN 2004). This study, conducted in 2007, examines the relationship and contribution of leadership integrity to the development of vision, mission and goal and in the implementation of human dimension of TQM. The sample consists of 698 respondents from 19 public MARA Higher Educational Institutions and 581 respondents from 16 private MARA Higher Educational Institutions in Malaysia. The respondents were randomly selected. Data were gathered using a questionnaire which was revised and adapted from previous instruments. Results showed that the element of leadership integrity has a positive and significant relationship with the development of vision, mission and goal and with the implementation of the human dimension of TQM Linear regression analysis revealed that leadership integrity is associated with the implementation of the human dimension of TQM elements and with the development of vision, mission and goal. The outcome of the study shows that MARA Higher Educational Institutions need integrity leadership to ensure implementation of TQM; and develop a valuesbased vision, mission and goal.